Phylogeny and ecology of the ubiquitous saprobe Cladosporium sphaerospermum, with descriptions of seven new species from hypersaline environments - Zalar, P. (CBS Fungal Biodiversity Centre, 2007)
Saprobic Cladosporium isolates morphologically similar to C. sphaerospermum are phylogenetically analysed on the basis of DNA sequences of the ribosomal RNA gene cluster, including the internal transcribed spacer regions ITS1 and ITS2, the 5.8S rDNA (ITS) and the small subunit (SSU) rDNA as well as β-tubulin and actin gene introns and exons. Most of the C. sphaerospermum-like species show halotolerance as a recurrent feature. Cladosporium sphaerospermum, which is characterised by almost globose conidia, is redefined on the basis of its ex-neotype culture. Cladosporium dominicanum, C. psychrotolerans, C. velox, C. spinulosum and C. halotolerans, all with globoid conidia, are newly described on the basis of phylogenetic analyses and cryptic morphological and physiological characters. Cladosporium halotolerans was isolated from hypersaline water and bathrooms and detected once on dolphin skin. Cladosporium dominicanum and C. velox were isolated from plant material and hypersaline water. Cladosporium psychrotolerans, which grows well at 4 °C but not at 30 °C, and C. spinulosum, having conspicuously ornamented conidia with long digitate projections, are currently only known from hypersaline water. We also newly describe C. salinae from hypersaline water and C. fusiforme from hypersaline water and animal feed. Both species have ovoid to ellipsoid conidia and are therefore reminiscent of C. herbarum. Cladosporium langeronii (= Hormodendrum langeronii) previously described as a pathogen on human skin, is halotolerant but has not yet been recorded from hypersaline environments.